Community perspectives on an internationally funded mangrove restoration project: Kien Giang province, Vietnam. (January 2016) - Nguyen, T.P.; Van Tam, Nguyen; Quoi, Le Phat; Parnell, Kevin E.
Abstract: It is common for environmental restoration projects to be reviewed by the administering organizations but it is much less common for the communities that the projects are meant to serve to detail their experiences and perceptions of the outcomes. We evaluate an internationally funded mangrove restoration project and reflect upon the lessons learned in regard to the project strategies and interventions, particularly from the perspective of the local community. The Vam Ray coast, Kien Giang Province, Vietnam, was seriously eroded by 2008. In May 2009, a demonstration project was established which achieved a high survival rate of transplanted mangroves and sea mud accumulation. This study used participatory action research methods (literature review, semi-structured interviews, field visits, and peer debriefing) to evaluate the project outcomes. Despite the project being generally very successful, its implementation and results were inadequately documented by agencies involved due in large part to insufficient local involvement during the reporting process, even though the local community was fully involved in the project planning and implementation. Inadequate documentation has led to mistakes being made when attempts have been made to replicate the project elsewhere, and incomplete findings have been incorporated into mangrove management plans at the provincial and regional levels. Using the community knowledge from the time of the project implementation and since, we detail the successes and problems encountered to provide more complete reporting, to assist transferability of the methods to other eroding muddy coasts in Vietnam and potentially elsewhere.